a) (x+6)^2-25
b) (-6, -25)
Step-by-step explanation:
Perfect square trinomial! If you have 12x, divide by two and get 6, so we have (x+6)^2+q. Then solve for q. You get q as -25.
For b, we just take the vertex from vertex form. We get x+6=0 so x=-6, and q = -25, so the answer is (-6, -25).
Hope that helped,
-sirswagger21
<u> 12x³ - 12x </u><u /> = 3/7 - 1/56x² - 3/7 = 3/7 - 3/7 - 1/56x² = -1/56x²
28x³ - 56x² + 28x
Answer:
48 divided by 16
Step-by-step explanation:
16 oz=1 lb
Divided by 16 because there are 16 oz per pound